A sensitivity study on the fire-induced heating of concrete slabs in composite floor systems. (May 2013) - Banerjee, Dilip K
The fire resistance of composite floor systems depends on the interaction of the concrete slab with steel beams. To evaluate the fire resistance of composite floor systems, the temporal and spatial variations of temperatures must be accurately determined. The temperature profiles in a concrete section are a function of concrete thermophysical properties and boundary conditions. However, there can be considerable uncertainty in their values. A sensitivity study using an orthogonal full-factorial design approach was conducted to determine which of these parameters most significantly influenced the thermal response of the slab. The time–temperature data from a Cardington fire test were used to validate a heat transfer model of a representative section of the composite floor system. The orthogonal factorial design analysis indicated that the thermal behavior of the concrete slab is most sensitive to, in decreasing order, thermal conductivity, effective emissivity, convective heat transfer coefficient at the exposed surface, and enthalpy.